The Effects of Tianjin's Openness on Economic Development in Beijing-Tianjin-Hebei Region Based on Extended Solow Model - Feng, Fan (International Journal of Economics and Financial Issues, 2016)
Opening has an important impact on economic development. However, due to the fact that various regions have different economic structure and development level, there are differences in the size of its actual effect. Using extended Solow model and 2002 --2013 panel data among 13 major cities of Beijing, Tianjin, and Hebei, this paper analyzed the effects of Tianjin's openness on economic development in Jing-Jin-Ji area. The result shows that improving the degree of Tianjin's openness has a very significant impact on the joint development of Jing-Jin-Ji area and regional economy. Therefore, we must further promote structural reforms and improve Tianjin's openness to give full play to its role in driving economic development in Jing-Jin-Ji area in the future. Keywords: Extended Solow model; Opening; Regional economic development; Economic growth JEL Classifications: F11; F43; O11